Reversible translocation of acyl-CoA:cholesterol acyltransferase (ACAT) between the endoplasmic reticulum and vesicular structures - Schiffmann, Andrea; Ahlswede, Lena; Gimpl, Gerald (Frontiers in Molecular Biosciences, 2023)
The enzyme acyl-CoA:cholesterol acyltransferase (ACAT) is normally localized in the endoplasmic reticulum (ER) where it can esterify cholesterol for storage in lipid droplets and/or the formation of lipoproteins. Here, we report that ACAT can translocate from the ER into vesicular structures in response to different ACAT inhibitors. The translocation was fast (within minutes), reversible and occurred in different cell types. Interestingly, oleic acid was able to fasten the re-translocation from vesicles back into the reticular ER network. The process of ACAT translocation could also be induced by cyclodextrins, cholesterol, lanosterol (but not 4-cholestene-3 one), 25-hydroxycholesterol, and by certain stress stimuli such as hyperosmolarity (sucrose treatment), temperature change, or high-density cultivation. In vitro esterification showed that ACAT remains fully active after it has been translocated to vesicles in response to hyperosmotic sucrose treatment of the cells. The translocation process was not accompanied by changes in the electrophoretic mobility of ACAT, even after chemical crosslinking.Interestingly, the protein synthesis inhibitor cycloheximide showed a stimulating effect on ACAT activity and prevented the translocation of ACAT from the ER into vesicles.